The wife's tale : a novel - Lansens, Lori. (New York : Little, Brown and Company, 2011)
Having gained weight and anxieties throughout her twenty- five-year marriage, Mary Gooch is dismayed when her husband fails to return home, a situation that compels Mary to locate and fight for him while combating unhealthy habits.
Originally published: Toronto : Knopf Canada, 2009.
Includes reader's guide.
Keywords: Wives -- Fiction; Self-actualization (Psychology) in women -- Fiction